Terson's Syndrome Due to Aneurismal Subarachnoid Hemorrhage - Hossain, Sanwar; Guda, Titus Leonard; Chowdhury, Forhad; Hossain, Md Somir (Anwer Khan Modern Medical College Journal, 2017)
Vitreous or retinal hemorrhage occurring in association with subarachnoid hemorrhage is known as Terson's syndrome. In Terson's syndrome, intracranial hemorrhages are followed by intraocular hemorrhage, classically in the subhyaloid space, but may also include subretinal, retinal, preretinal, and vitreal collections. Usually occurs in adult, but can be at any age. It may be unilateral or bilateral. Vitreous hemorrhage recovery is usually spontaneous within 6 to 12 months, otherwise vitrectomy is considered. We report a case of Terson's syndrome which was admitted in Anwer Khan Modern Medical College & Hospital as unilateral Terson's syndrome with multiple intra retinal hemorrhage of left eye associated with Hypertension & Diabetes Mellitus. Anwer Khan Modern Medical College Journal Vol. 8, No. 2: Jul 2017, P 153-156